El recurso de insistencia en Colombia como mecanismo para acceder a la información pública (2016)
This article contains a legal analysis of a mechanism, which although known, has not been extensively studied in depth. It's the appeal of insistence in Colombian law, instituted in order to allow that in this case, the administrative judges, enter a judicial authority, to study the bases under which public entities denied providing information, especially if the aforementioned reserve justifies the restriction.